Synthetic accesses to biguanide compounds - Grytsai, Oleksandr; Ronco, Cyril; Benhida, Rachid (Beilstein Journal of Organic Chemistry, 2021)
Biguanide is a unique chemical function, which has attracted much attention a century ago and is showing resurgent interest in recent years after a long period of dormancy. This class of compounds has found broad applications such as reaction catalysts, organic strong bases, ligands for metal complexation, or versatile starting materials in organic synthesis for the preparation of nitrogen-containing heterocycles. Moreover, biguanides demonstrate a wide range of biological activities and some representatives are worldwide known such as metformin, the first-line treatment against type II diabetes, or chlorhexidine, the gold standard disinfectant and antiseptic. Although scarcely represented, the number of “success stories” with biguanide-containing compounds highlights their value and their unexploited potential as future drugs in various therapeutic fields or as efficient metal ligands. This review provides an extensive and critical overview of the synthetic accesses to biguanide compounds, as well as their comparative advantages and limitations. It also underlines the need of developing new synthetic methodologies to reach a wider variety of biguanides and to overcome the underrepresentation of these compounds.
Keywords: amidine; biguanide; guanidine chemistry; metformin derivatives; polynitrogen ligands; synthetic methodology

(untitled) - Kathuria, D.; Bankar, A. A.; Bharatam, P. V. (J. Mol. Struct., 2018)

Oral Antidiabetics - Kuhlmann, J.; Puls, W. (Springer, 1996)

Stabilité et voies de dégradation du chlorhydrate de metformine - Poirée, M. A. (Ecole Pratique des Hautes Etudes, 1991)

(untitled) - Rathke, B. (Ber. Dtsch. Chem. Ges., 1879)

(untitled) - Gelbard, G.; Vielfaure-Joly, F. (Tetrahedron Lett., 1998)

(untitled) - Ishikawa, T.; Harwood, L. M. (Synlett, 2013)

Metal and non-metal biguanide complexes - Ray, R. K.; Kauffman, G. B.; Ray, R. K. (New Age International Ltd., 1999)

(untitled) - Ray, P. (Chem. Rev., 1961)

(untitled) - Slotta, K. H.; Tschesche, R. (Ber. Dtsch. Chem. Ges. B, 1929)

(untitled) - Katritzky, A. R.; Tala, S. R.; Singh, A. (ARKIVOC, 2010)

(untitled) - Elpern, B. (Ann. N. Y. Acad. Sci., 1968)

The Chemistry of Biguanides - Kurzer, F.; Pitchfork, E. D. (Springer, 1968)

(untitled) - Herth, R. (Monatsh. Chem., 1880)

(untitled) - Smolka, A.; Friedreich, A. (Monatsh. Chem., 1888)

(untitled) - Bamberger, E.; Dieckmann, W. (Ber. Dtsch. Chem. Ges., 1892)

(untitled) - Hokfelt, B.; Jonsson, A. (J. Med. Chem., 1962)

(untitled) - Shapiro, S. L.; Parrino, V. A.; Freedman, L. (J. Am. Pharm. Assoc., Sci. Ed., 1957)

(untitled) - Tonelli, M.; Espinoza, S.; Gainetdinov, R. R.; Cichero, E. (Eur. J. Med. Chem., 2017)

(untitled) - Cohn, G. (Chem.-Ztg., 1911)

(untitled) - Böttcher, T.; Kolodkin-Gal, I.; Kolter, R.; Losick, R.; Clardy, J. (J. Am. Chem. Soc., 2013)

(untitled) - van Kuijk, S. J. A.; Parvathaneni, N. K.; Niemans, R.; van Gisbergen, M. W.; Carta, F.; Vullo, D.; Pastorekova, S.; Yaromina, A.; Supuran, C. T.; Dubois, L. J.; Winum, J.-Y.; Lambin, P. (Eur. J. Med. Chem., 2017)

(untitled) - Chen, H.; Dao, P.; Laporte, A.; Garbay, C. (Tetrahedron Lett., 2010)

(untitled) - Singh, S.; Wanjari, P. J.; Bhatia, S.; Sonwane, V. C.; Chakraborti, A. K.; Bharatam, P. V. (Med. Chem. Res., 2015)

(untitled) - Mayer, S.; Daigle, D. M.; Brown, E. D.; Khatri, J.; Organ, M. G. (J. Comb. Chem., 2004)

(untitled) - Zhou, S.; Xu, L.; Cao, M.; Wang, Z.; Xiao, D.; Xu, S.; Deng, J.; Hu, X.; He, C.; Tao, T.; Wang, W.; Guan, A.; et al. (Arch. Pharm. (Weinheim, Ger.), 2019)

(untitled) - Obianom, O. N.; Coutinho, A. L.; Yang, W.; Yang, H.; Xue, F.; Shu, Y. (Mol. Pharmaceutics, 2017)

WO Pat. Appl. - Kim, S. W.; Kim, H. W.; Yoo, S. H.; Lee, J. S.; Heo, H. J.; Lee, H. B.; Kook, J. A.; Lee, Y. W.; Kim, M. J.; Cho, W. (Guanidine compounds and use thereof, 2015)

(untitled) - Zeng, Z.; Wang, R.; Twamley, B.; Parrish, D. A.; Shreeve, J. M. (Chem. Mater., 2008)

(untitled) - Smith, G. B. L.; Kane, J. H.; Mason, C. W. (J. Am. Chem. Soc., 1929)

(untitled) - Dolzhenko, A. V.; Dolzhenko, A. V.; Chui, W.-K. (ChemInform, 2006)

(untitled) - Soliman, A. M.; Mohamed, S. K.; El-Remaily, M. A. E. A. A. A.; Abdel-Ghany, H. (J. Heterocycl. Chem., 2014)

(untitled) - Grytsai, O.; Druzhenko, T.; Demange, L.; Ronco, C.; Benhida, R. (Tetrahedron Lett., 2018)

(untitled) - Baladi, T.; Hamouda‐Tekaya, N.; Gonçalves, L. C. P.; Rocchi, S.; Ronco, C.; Benhida, R. (ChemMedChem, 2020)

(untitled) - Davoll, J.; Johnson, A. M. (J. Chem. Soc. C, 1970)

(untitled) - Bardovskyi, R.; Grytsai, O.; Ronco, C.; Benhida, R. (New J. Chem., 2020)

(untitled) - Mohamed, S. K.; Soliman, A. M.; El Remaily, M. A. A.; Abdel-Ghany, H. (J. Heterocycl. Chem., 2013)

(untitled) - Shestakov, A. S.; Prezent, M. A.; Zlatoustovskaya, E. O.; Shikhaliev, K. S.; Falaleev, A. V.; Sidorenko, O. E. (Chem. Heterocycl. Compd., 2015)

(untitled) - Curd, F. H. S.; Rose, F. L. (J. Chem. Soc., 1946)

U.S. Patent - Curd, F. H. S.; Rose, F. L. (N1-Aryl-N5-Dialkyl Biguanides, 1951)

U.S. Pat. Appl. - Curd, F. H. S.; Rose, F. L. (Biguanide compounds, 1950)

U. S. Pat. Appl. - Curd, F. H. S.; Rose, F. L. (Biguanide derivatives, 1950)

(untitled) - Prati, F.; De Simone, A.; Armirotti, A.; Summa, M.; Pizzirani, D.; Scarpelli, R.; Bertozzi, S. M.; Perez, D. I.; Andrisano, V.; Perez-Castillo, A.; Monti, B.; Massenzio, F.; et al. (ACS Chem. Neurosci., 2015)

(untitled) - Loesche, A.; Wiese, J.; Sommerwerk, S.; Simon, V.; Brandt, W.; Csuk, R. (Eur. J. Med. Chem., 2017)

(untitled) - Rathke, B. (Ber. Dtsch. Chem. Ges., 1878)

(untitled) - Suyama, T.; Soga, T.; Miyauchi, K. (ChemInform, 1989)

(untitled) - Lebel, O.; Maris, T.; Perron, M.-È.; Demers, E.; Wuest, J. D. (J. Am. Chem. Soc., 2006)

(untitled) - Zhou, Y.; Ma, J.; Lin, X.; Huang, X.-P.; Wu, K.; Huang, N. (J. Med. Chem., 2016)

(untitled) - Štrukil, V.; Glasovac, Z.; Đilović, I.; Matković-Čalogović, D.; Šuman, L.; Kralj, M.; Eckert-Maksić, M. (Eur. J. Org. Chem., 2012)

(untitled) - Huttunen, K. M.; Leppänen, J.; Kemppainen, E.; Palonen, P.; Rautio, J.; Järvinen, T.; Vepsäläinen, J. (Synthesis, 2008)

(untitled) - Petersen, H. J.; Nielsen, C. K.; Arrigoni-Martelli, E. (J. Med. Chem., 1978)

(untitled) - Rose, F.; Swain, G. (J. Chem. Soc., 1956)

(untitled) - Lebel, O.; Perron, M.-È.; Maris, T.; Zalzal, S. F.; Nanci, A.; Wuest, J. D. (Chem. Mater., 2006)

(untitled) - McMorran, D. A.; McAdam, C. J.; van der Salm, H.; Gordon, K. C. (Dalton Trans., 2013)

(untitled) - Britz, J.; Meyer, W. H.; Wegner, G. (Adv. Mater. (Weinheim, Ger.), 2010)

WO Pat. Appl. - Pietras, R. J.; Jung, M. E.; Marquez-Garban, D. C.; Deng, G. (Compounds And Methods Of Treating Cancer, 2013)

WO Pat. Appl. - Konteatis, Z. D.; Popovici-Muller, J.; Travins, J. M.; Zahler, R.; Cai, Z.; Zhou, D. (Therapeutically Active Compounds And Their Methods Of Use, 2015)

(untitled) - Rembarz, G.; Brandner, H.; Finger, H. (J. Prakt. Chem., 1964)

(untitled) - Maeda, S.; Kita, T.; Meguro, K. (J. Med. Chem., 2009)

(untitled) - Xiao, D.; Lu, Z.; Wang, Z.; Zhou, S.; Cao, M.; Deng, J.; Hu, X.; Peng, M.; He, C.; Wu, J.; Xu, S.; Zhang, H.; et al. (Bioorg. Med. Chem., 2020)

(untitled) - Gräber, M.; Hell, M.; Gröst, C.; Friberg, A.; Sperl, B.; Sattler, M.; Berg, T. (Angew. Chem., Int. Ed., 2013)

WO Patent - Kim, S. W.; Kim, H. W.; Lee, J. S.; Lee, H. B.; Lee, Y. W. (Guanidine Compounds And Use Thereof, 2016)

(untitled) - Rosowsky, A.; Papathanasopoulos, N. (J. Org. Chem., 1974)

(untitled) - Jones, M. L.; Kuyper, L. F.; Styles, V. L.; Caddell, J. M. (J. Heterocycl. Chem., 1994)

(untitled) - Kumar, A. S.; Sasidharan, N.; Ganguly, R.; Leow, D.; Hng, H. H. (New J. Chem., 2018)

(untitled) - Liu, W.; Lin, Q.-h.; Li, Y.-c.; Chen, P.-w.; Fang, T.; Zhang, R.-b.; Pang, S.-p. (Sci. Rep., 2015)

U. S. Patent - Schenker, E.; Hasspacher, K. (4-Phenylpiperidine Biguanides, 1970)

(untitled) - Bredereck, H.; Effenberger, F.; Hofmann, A.; Hajek, M. (Angew. Chem., Int. Ed. Engl., 1963)

(untitled) - Bernatowicz, M. S.; Wu, Y.; Matsueda, G. R. (J. Org. Chem., 1992)

(untitled) - Igashira-Kamiyama, A.; Kajiwara, T.; Nakano, M.; Konno, T.; Ito, T. (Inorg. Chem., 2009)

(untitled) - Edmont, D.; Rocher, R.; Plisson, C.; Chenault, J. (Bioorg. Med. Chem. Lett., 2000)

(untitled) - Vaillancourt, V. A.; Larsen, S. D.; Tanis, S. P.; Burr, J. E.; Connell, M. A.; Cudahy, M. M.; Evans, B. R.; Fisher, P. V.; May, P. D.; Meglasson, M. D.; Robinson, D. D.; Stevens, F. C.; et al. (J. Med. Chem., 2001)

WO Patent - Teintze, M.; Wilkinson, R. A.; Labib, M. (N-Alkyl Or N-Aryl Substituted Guanide And Biguanide Compounds And Methods Of Their Use, 2012)

(untitled) - Turner, R. (Synthesis, 1975)

(untitled) - Suyama, T.; Okuno, S.; Kariya, M.; Ichikawa, E. (Nippon Kagaku Kaishi, 1987)

(untitled) - Suyama, T.; Iwaoka, T.; Yatsurugi, T.; Ichikawa, E. (Nippon Kagaku Kaishi, 1986)

(untitled) - Tilley, J. W.; Ramuz, H.; Levitan, P.; Blount, J. F. (Helv. Chim. Acta, 1980)

Korean Pat. Appl. - Kim, S. U.; Kim, H. U.; Yoo, S. H.; Heo, H. J.; Lee, H. B.; Kim, H. U. (Preparation of aryl guanidine derivatives as IDO-1 inhibitor, 2017)

(untitled) - Richter, R.; Ulrich, H. (J. Org. Chem., 1981)

WO Patent - Sakai, N.; Yanaba, K.; Arimitsu, K. (Base generator, base-reactive composition containing said base generator, and base generation method, 2014)

(untitled) - Glasovac, Z.; Trošelj, P.; Jušinski, I.; Margetić, D.; Eckert-Maksić, M. (Synlett, 2013)

(untitled) - Yavari, I.; Nematpour, M. (Mol. Diversity, 2015)

(untitled) - Štrukil, V.; Đilović, I.; Matković-Čalogović, D.; Saame, J.; Leito, I.; Šket, P.; Plavec, J.; Eckert-Maksić, M. (New J. Chem., 2012)

(untitled) - Kurzer, F.; Pitchfork, E. D. (J. Chem. Soc., 1964)

(untitled) - Kurzer, F.; Douraghi-Zadeh, K. (J. Chem. Soc. C, 1967)

(untitled) - Pottabathula, S.; Royo, B. (Tetrahedron Lett., 2012)

(untitled) - Zhang, W.-X.; Nishiura, M.; Hou, Z. (Chem. – Eur. J., 2007)

(untitled) - Chen, J.; Wang, Y.; Luo, Y. (Chin. J. Chem., 2013)

(untitled) - Baraldi, P. G.; Baraldi, S.; Saponaro, G.; Aghazadeh Tabrizi, M.; Romagnoli, R.; Ruggiero, E.; Vincenzi, F.; Borea, P. A.; Varani, K. (J. Med. Chem., 2015)

(untitled) - Dorokhov, V. A.; Lavrinovich, L. I.; Mikhailov, B. M. (Bull. Acad. Sci. USSR, Div. Chem. Sci. (Engl. Transl.), 1980)

(untitled) - Birtwell, S.; Curd, F. H. S.; Rose, F. L. (J. Chem. Soc., 1949)

(untitled) - Hume, W. E.; Shingaki, T.; Takashima, T.; Hashizume, Y.; Okauchi, T.; Katayama, Y.; Hayashinaka, E.; Wada, Y.; Kusuhara, H.; Sugiyama, Y.; Watanabe, Y. (Bioorg. Med. Chem., 2013)

(untitled) - Koh, M.; Lee, J.-C.; Min, C.; Moon, A. (Bioorg. Med. Chem., 2013)

(untitled) - Shirai, K.; Sugino, K. (J. Org. Chem., 1960)

(untitled) - Wang, Z.; Huynh, H. K.; Han, B.; Krishnamurthy, R.; Eschenmoser, A. (Org. Lett., 2003)

WO Patent - Daifuku, R.; Gall, A.; Sergueev, D. (Mutagenic heterocycles, 2005)

WO Pat. Appl. - Kim, H. W.; Jeong, J. K.; Lee, J. S.; Heo, H. J.; Lee, H. B.; Kook, J. A.; Kim, S. W.; Son, M. (Biguanide compound and use thereof, 2016)

(untitled) - Abdel-Monem, W. R.; Ali, T. E. (Int. J. Chem. (Calcutta, India), 2007)

(untitled) - El-Kashef, H.; Farghaly, A.-R.; Al-Hazmi, A.; Terme, T.; Vanelle, P. (Molecules, 2010)

(untitled) - El-Gendy, Z.; Morsy, J. M.; Allimony, H. A.; Abdel-Monem, W. R.; Abdel-Rahman, R. M. (Phosphorus, Sulfur Silicon Relat. Elem., 2003)

(untitled) - Zhang, L.; Sathunuru, R.; Caridha, D.; Pybus, B.; O’Neil, M. T.; Kozar, M. P.; Lin, A. J. (J. Med. Chem., 2011)

(untitled) - Unangst, P. C.; Connor, D. T.; Cetenko, W. A.; Sorenson, R. J.; Kostlan, C. R.; Sircar, J. C.; Wright, C. D.; Schrier, D. J.; Dyer, R. D. (J. Med. Chem., 1994)

(untitled) - Zhang, L.; Sathunuru, R.; Luong, T.; Melendez, V.; Kozar, M. P.; Lin, A. J. (Bioorg. Med. Chem., 2011)

(untitled) - Garnier, E.; Audoux, J.; Pasquinet, E.; Suzenet, F.; Poullain, D.; Lebret, B.; Guillaumet, G. (J. Org. Chem., 2004)

(untitled) - Alijevic, O.; Hammoud, H.; Vaithia, A.; Trendafilov, V.; Bollenbach, M.; Schmitt, M.; Bihel, F.; Kellenberger, S. (ACS Chem. Neurosci., 2018)

(untitled) - Kotb, A.; Abutaleb, N. S.; Seleem, M. A.; Hagras, M.; Mohammad, H.; Bayoumi, A.; Ghiaty, A.; Seleem, M. N.; Mayhoub, A. S. (Eur. J. Med. Chem., 2018)

(untitled) - El-Tombary, A. A.; Ismail, K. A.; Aboulwafa, O. M.; Omar, A.-M. M. E.; El-Azzouni, M. Z.; El-Mansoury, S. T. (Farmaco, 1999)

(untitled) - Molina, P.; Alajarin, M.; Lopez-Leonardo, C.; Foces-Foces, M. d. l. C.; Cano, F. H.; Claramunt, R. M.; Elguero, J. (J. Org. Chem., 1989)

(untitled) - Molina, P.; Alajarin, M.; Lopez-Leonardo, C.; Elguero, J.; Claramunt, R. M. (Tetrahedron, 1987)

(untitled) - Beeley, H. A.; Degorce, S.; Harris, C. S.; Lecoq, J.; Morgentin, R.; Perkins, D. (Tetrahedron Lett., 2013)